Life Prediction of AMT Shifting- gear Case based on the Real Measured Load Spectrum - Yang Ping; Cheng Yunchuan; Shi Xiaohui; Zou Xihong (Jixie chuandong)
By taking the AMT transmission shifting- gear case as a studying object and taking the influence of the engine and road vibration into account,the vibration load spectra of AMT are collected in Xiangyang Proving Ground through reasonably installed the sensors. Besides,the pretreatment and repeatability checking of load spectra is carried out. Through the comparison of different load spectrum stress,it is found that several measuring points are dangerous point,so that should focus on these place when designing. Combining with the fatigue damage theory,the fatigue life of target point is calculated and analyzed,and it has an important significance to improve the reliability of product.